The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1515/humo-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

The report and analysis of the First U21 European Deaf Football Championship Men, Wroclaw, Poland 2016

Abstract: The First U21 European Deaf Football Championship Men was played in August 2016 in Wroclaw, Poland. No studies have documented or analysed sporting events for deaf players at the elite level. The aim of the study was to bring deaf football closer to the reader and analyse selected offensive actions recorded during the U21 Championship.Analyses were performed on the basis of video recordings from the stadium. Eight national teams participated in the Championship. Sixteen matches were analysed with reference to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Some times for Paralympics competitors. A review of databases of scientific journals has identified only several publications concerning hard-of-hearing players and teams (Milašius et al, 2014;Palmer et al, 2006;Steward et al, 1991;Szulc, 2017Szulc, , 2019Szulc et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some times for Paralympics competitors. A review of databases of scientific journals has identified only several publications concerning hard-of-hearing players and teams (Milašius et al, 2014;Palmer et al, 2006;Steward et al, 1991;Szulc, 2017Szulc, , 2019Szulc et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…the aim of the work was to determine the offensive potential of teams participating in the 2 nd EDsO U21 in stockholm. the obtained results were compared with the level of offensive acts that took place during the 1 st EDsO U21 in Wroclaw [16]. Additionally, the results of matches and offensive actions were compared with those reported during the UEFA Under 21 championship in the czech republic (2015) [17] and in Poland (2017) [18].…”
Section: Introductionmentioning
confidence: 99%